Development and Evaluation of Rapid and Accurate CRISPR/Cas13-Based RNA Diagnostics for Pneumocystis jirovecii Pneumonia - Zhan, Yangqing; Gao, Xiaoqing; Li, Shaoqiang; Si, Yeqi; Li, Yuanxiang; Han, Xu; Sun, Wenjun; Li, Zhengtu; Ye, Feng (Frontiers in Cellular and Infection Microbiology, 2022)
Background Pneumocystis jirovecii can result in a serious pulmonary infection, Pneumocystis jirovecii pneumonia, in immunocompetent hosts. The diagnosis of Pneumocystis jirovecii pneumonia has long been a major clinical concern, and there are limitations with the currently utilized immunostaining and polymerase chain reaction diagnosis/detection technologies (e.g., insufficient sensitivity and accuracy). Hence, we sought to establish a rapid and RNA-specific transcription mediated amplification and CRISPR/Cas13a-based diagnostics targeted P. jirovecii-mitochondrial large subunit ribosomal RNA. Methods The procedure of the diagnostics included amplification of the extracted RNA samples by transcription mediated amplification, followed by CRISPR/Cas13 detection, and ultimately, the judgment of the results after 30 minutes of fluorescence signal. Later, the diagnostic performance of the CRISPR/Cas13-based diagnostics were tested on the 62 surplus clinical samples. Results This CRISPR/Cas13-based diagnostics achieved limits of detection of approximately 2 copies/µL transcribed RNA templates, with no cross reaction to other respiratory pathogens, including bacteria and fungi. Similar to in-house quantitative real-time polymerase chain reaction, CRISPR/Cas13-based diagnostics was still positive in 243-fold diluted bronchial alveolar lavage fluid. A preliminary evaluation of 62 surplus bronchial alveolar lavage fluid samples from patients suspected of Pneumocystis jirovecii pneumonia showed that CRISPR/Cas13-based diagnostics achieved a 78.9% sensitivity and a 97.7% specificity in the diagnosis of Pneumocystis jirovecii pneumonia. Conclusion Our study demonstrates that the CRISPR/Cas13-based diagnostics technique has good performance for the accurate and specific diagnosis of Pneumocystis jirovecii pneumonia.